Phytochemical and pharmacological properties of rambutan (Nappecium lappaceum L.) and its industrial usage : A mini review - Yasmin Amirah, Che Yahaya; Normaiza, Zamri; Aini Norhidayah, Mohamed (AIP Publishing, 2024)
Rambutan, a famous tropical fruit, contains a high concentration of bioactive chemicals. Most of the components from this plant including leaves, pulp and seed have many uses and are thought to have medicinal properties.Bioactive components or phytochemicals (such as polyphenols, flavonoids, vital minerals, and vitamins) are found in most tropical fruits, as well as their bioactivity. Thus, this review study aims to give a general description of the phytochemical contents, medicinal qualities of rambutan trees and prospective industrial applications.